Challenges for information technology supporting educational assessment. (9th September 2013) - Webb, M.; Gibson, D.; Forkosh‐Baruch, A.
Abstract: This article examines the scope for IT‐enabled assessments to serve simultaneously both learners and the enterprise of education. The article proposes ways of combining frameworks that come from two different perspectives: 1) a conceptual approach to assessment design for computerized assessment based on evidence‐centred design (ECD) and 2) a framework for formative assessment based on empirical research in classrooms. The article argues that combining the ECD and formative assessment frameworks and building on the opportunities provided by computerized assessments as well as harnessing teachers' and students' experience and developing their validation processes could enable assessments to address simultaneously assessment FOR learning and assessment OF learning. Strategies would include harnessing the benefits of embedded continuous unobtrusive measuring of performance while learners are engaged in interesting computerized tasks designed to support their learning. Learners need to be involved in discussing and negotiating their learning so we conceptualize these embedded unobtrusive processes as 'quiet assessment', whose volume can be turned up by learners whenever they wish, to give them access to meaningful representations of evidence and arguments about their achievements. These strategies could enable a wider range of measures to contribute to judgements of students' achievements, thus supporting their learning in 21st‐century contexts.